Women write : a mosaic of women's voices in fiction, poetry, memoir, and essay - Cahill, Susan, 1940- (New York : New American Library, 2004)
A dazzling collection of the finest literature from female writers, from Jane Austen and Virginia Woolf to Toni Morrison and Lorrie Moore, also includes Mary Shelley, Emily Dickinson, Maya Angelou, Toni Morrison, and Sylvia Plath. This wide ranging collection features the most brilliant fiction, poetry, memoir, letters, and essays by women writers with a pitch perfect ear and a rich understanding of the unique female perspective.
Anne Bradstreet -- Margaret Cavendish -- Aphra Behn -- Lady Mary Wortley Montagu -- Mary Wollstonecraft -- Mary Shelley -- Margaret Fuller -- Harriet A. Jacobs -- Frances E. W. Harper -- Emily Dickinson -- Sarah Orne Jewett -- Edith Wharton -- Willa Cather -- Virginia Woolf -- Marianne Moore -- Katherine Mansfield -- Zora Neale Hurston -- Edna St. Vincent Millay -- Louise Bogan -- Stevie Smith -- Kathleen Raine -- Eudora Welty -- Mary Lavin -- Tillie Olsen -- Muriel Spark -- Grace Paley -- Marie Ponsot -- Nadine Gordimer -- Denise Levertov -- Flannery O'Connor -- Anne Sexton -- Maya Angelou -- Cynthia Ozick -- Adrienne Rich -- Toni Morrison -- Alice Munro -- Edna O'Brien -- Sylvia Plath -- Mary Oliver -- June Jordan -- Marge Piercy -- Joyce Carol Oates -- Angela Carter -- Sharon Olds -- Alice Walker -- Leslie Marmon Silko -- Sandra Cisneros -- Gish Jen -- Lorrie Moore -- Andrea Lee.
"NAL books."
Keywords: English literature -- Women authors; American literature -- Women authors; Women -- Literary collections; Women -- Biography; Women